TYPOLOGY OF VILLAGE BASED LIVELIHOODS IN V KOTO DISTRICT MUKOMUKO REGION - EFENDI, SAKRI; DRS. Bakaruddin, Ms, DRS. Bakaruddin, Ms; Despica, S.Pd., M.Si, Rika (STKIP PGRI Sumbar, 2014)
ABSTRACT This study aims to determine typology of village based livelihood in V Koto District Mukomuko region based on : 1) the livelihoods of rice field, 2) the livelihoods of dryland agriculture and 3) livelihood plantations.This research is descriptive evaluative, which describes the existing conditions and compare with the ideal conditions (evaluative). The population in this study was the entire village in V Koto District Mukomuko region and the subject is the whole village and the village chief district officer BPS of Mukomuko.The results of the study found that : (1) Typology of rural livelihoods based livelihood views of rice fields in V Koto District Mukomuko region, no village can be grouped into the village rice fields, as a percentage score for village rice fields smaller than the plantation village, (2 ) typology based livelihood village seen from dry land farming livelihoods in V Koto District Mukomuko region, then nothing can be grouped into dryland farming villages and (3) rural typology based livelihood views of livelihood plantations in V Koto District Mukomuko region, the whole village is a group of villages because of the vast plantation estates and land use is dominated by oil palm and rubber plants.